Reliability and Validation of a Chinese Version of the Sleep Disturbance Scale for Children in Preschoolers - CHEN Xianrui, LIN Xiaoxia, XU Ping, CHEN Yanhui, CHEN Shan, YAO Yonghua (Zhongguo quanke yixue, 2023)
Background There are less studies on sleep disturbance and limited effective screening and assessment scales for sleep disturbance in Chinese preschoolers. Objective To assess the reliability and validity of the Chinese version of Sleep Disturbance Scale for Children (SDSC-C) in Chinese preschoolers, providing evidence for expanding the application of SDSC in preschoolers. Methods By use of convenience sampling, preschool children (3-5 years old) were selected as survey participants for testing the psychometrics of the draft of the SDSC-C from one urban community and one rural community in each of five cities (Fuzhou, Quanzhou, Longyan, Sanming and Nanping) of Fujian Province from June to November 2021 with the assistance of the Fujian Family Planning Association Network, and their parents were selected as their agents to complete the questionnaire survey. Then its items were modified, screened and evaluated by an expert group, after that, the draft was developed into a formal version consisting of six domains and 23 items. The reliability and validity of the scale were assessed by item analysis, reliability analysis, validity analysis, exploratory factor analysis, and confirmatory factor analysis. Results The survey obtained a response rate of 92.04% (370/402) . The high-score group〔n=106, ranked the top 27% in terms of total score of SDSC-C (≥49 points) 〕and low-score group〔n=113, ranked the bottom 27% in terms of total score of SDSC-C (≤37 points) 〕divided by critical ratio method had significant differences in the score of each item of the SDSC-C (P<0.05) . The Cronbach's α of the scale was 0.86, with 0.87 of estimating interrater agreement. The I-CVI for each item was >0.78, with kappa values were > 0.74. The S-CVI/UA was 0.87 and S-CVI/Ave was 0.98. For SDSC-C , KMO= 0.85, results of Bartlett's test of sphericity were χ2=3 013.30, P<0.001. By principal component analysis, 7 factors with an engivalue >1 were extracted, explaining 65.125% of the total variance. However, a six-factor solution (i.e. six types of sleep disorder) based on parent-reported sleep disorder symptoms in our study indicated the factor loading of items ranged from 0.34-0.85, which could explain 60.539% of the total variance. The confirmatory factor analysis showed the values of fitting indicator as follows: χ2/DF=2.66, CFI=0.84, TLI=0.81, SRMR=0.08, and RMSEA=0.08. Conclusion This study revealed that the SDSC-C is a valid and reliable scale that can provide a comprehensive and detailed assessment of sleep disturbances in Chinese preschool children, which is beneficial to clinicians for early screening and assessment of sleep-related problems in preschool children.